Alteration of unfolded protein responses and autophagy signaling represented the molecular basis underlying saccharin toxicity to Drosophila (Diptera: Drosophilidae). Issue 4 (1st July 2021) - Osabutey, Angelina F.; Kim, A‐Young; Seo, Bo Yoon; Mai, Linh Xuan; Koh, Young Ho
Abstract: The purpose of this study was to develop a new control method for Drosophila using saccharin sodium dihydrate (saccharin), an artificial sweetener that is safe for humans and the environment, and to elucidate its mode of action. In this study, we confirmed that saccharin can dose‐dependently inhibit the development of or kill vinegar flies (VFs) and spotted wing Drosophila (SWDs). In addition, we found that low concentrations of saccharin induced a similar effect as starvation in Drosophila, whereas high concentrations of saccharin induced changes in the unfolded protein response (UPR) and autophagy signaling that were unlike starvation and inhibited development or killed the VF and the SWD by performing real‐time quantitative polymerase chain reaction analyses. Spinosad is a widely used plant protection agent for SWD control. When saccharin was cotreated with 0.25–1.0 ppm spinosad, an additive insecticidal activity was observed only at high concentrations of saccharin. However, when saccharin was cotreated with 2.0 ppm spinosad, an additive insecticidal activity was observed at low concentrations of saccharin. Taken together, alteration of UPR and autophagy signaling represented the molecular basis underlying saccharin toxicity to Drosophila and concurrent spraying of an insecticide with saccharin could enhance the insecticidal activities. Abstract : Saccharin induced developmental retardation of the 3rd instar vinegar fly (VF) larvae and alteration in the autophagy and the unfolded protein response signaling in their fat bodies. In addition, when saccharin was mixed with spinosad, toxicity to VF, and spotted wing Drosophila (SWD) was increased even at low concentrations of saccharin. Research Highlights: Saccharin inhibits the development of vinegar fly (VF) and spotted wing Drosophila (SWD) larvae and is toxic to adult Drosophila . Saccharin induces abnormalities in the autophagy and the unfolded protein response (UPR) signaling of the Drosophila fat body. The toxicity of saccharin to Drosophila was increased by simultaneous treatment with spinosad.